Potentially active aspirin derivative to release nitric oxide: In-vitro, in-vivo and in-silico approaches - Amruta M. Amritkar; Afzal Hussain; Mohammad A. Altamimi; Sumel Ashique; Mohd Usman Mohd Siddique; Sushil Burle; Anwar R. Shaikh; Sameer N. Goyal; Zahid R. Bhat (Elsevier, 2024)
The series of newer salicylate derivatives incorporating nitroxy functionality were synthesized and evaluated for their potential effect in gastrointestinal (GI) related toxicity produced by aspirin. The synthesized compounds (5a-j) were subjected to %NO (nitric oxide) release study, in-vitro anti-inflammatory potential, % inhibition of carrageenan-induced paw edema and the obtained results were validated by in-silico studies including molecular docking, MD simulations and in-silico ADME (absorption, distribution, metabolism, and elimination) calculations. Compounds 5a (20.86 %) and 5g (18.20 %) displayed the highest percentage of NO release in all the tested compounds. Similarly, 5a and 5h were found to have (77.11 % and 79.53 %) &(78.56 % and 66.10 %) inhibition in carrageenan induced paw edema in animal mode which were relatively higher than ibuprofen (standard used). The obtained results were validated by molecular docking and MD simulations studies. The molecular docking study of 5a and 5h revealed that docking scores were also obtained in very close proximity of −8.35, −9.67 and −8.48 for ibuprofen, 5g and 5h respectively. In MD simulations studies, the calculated lower RMSD (root mean square deviation) values 2.8 Å and 5.6 Å for 5g and 5h, respectively indicated the stability of ligand-protein complexes. Similarly lower RSMF (root mean square fluctuation) values indicated the molecules remained in the active pocket throughout the entire MD simulations run. Further, in-silico ADME calculations were determined and all compounds obey the Lipinski's rule of five and it was predicted that these molecules would be orally active without any serious toxic effect.